Integration of metabolomics and transcriptomics to reveal anti-immunosuppression mechanism of Lycium barbarum polysaccharide - Wang, Jiandong; Zhang, Xue; Wu, Yi; Wei, Qianfei; Yan, Lingshan; Yu, Youli; Guo, Yanan; Yu, Zhengqin; Wang, Pan; Yang, Xiaonan (Frontiers in Pharmacology, 2024)
It is well documented that immunosuppression in chickens increases the risk of secondary infections and immunodeficiencies, resulting in significant financial setbacks for the poultry sector. It is crucial to determine if Lycium barbarum polysaccharide (LBP) can counteract immune suppression in young chickens, considering its known ability to modulate immune responses. The aim of this study was to investigate the antagonistic effect and mechanism of LBP on immunosuppression in chicks. A total of 200 seven-day-old Hyland Brown laying hens were used to develop an immunosuppression model and to investigate the optimal time of use and optimal dosage of LBP. A further 120 seven-day-old Hyland Brown laying hens were used to investigate the mechanism of antagonism of LBP against immunosuppression at the optimal time and dosage. The results demonstrated that LBP significantly elevated body weight, spleen index, and peripheral lymphocyte transformation rate, and ameliorated pathological spleen damage in immunosuppressed chickens. A total of 178 differential genes were significantly up-regulated following LBP intervention, with a significant enrichment in immunerelated pathways, including the chemokine signalling pathway, the C-type lectin receptor signalling pathway, the B-cell receptor signalling pathway, platelet activation, natural killer cell-mediated cytotoxicity, and Th1 and Th2 cell differentiation. A total of 20 different metabolites were identified by metabolomics, which were mainly involved in vitamin metabolism, lipid metabolism, nucleic acid metabolism and amino acid metabolism. The integrated examination of transcriptomic and metabolomic data revealed that the glycerophospholipid metabolic pathway stands out as the most significant among all metabolic pathways. The results demonstrated that LBP regulate the immune system in a multi-pathway and multi-target way.